Hydrolyzed whey protein enriched with glutamine dipeptide attenuates skeletal muscle damage and improves physical exhaustion test performance in triathletes - Pinheiro Peres, F.; Levada-Pires, A. C.; Vieira, M.; Hatanaka, E.; Cury-Boaventura, M. F.; Folador, A.; Gorjão, R.; Hirabara, S. M.; Santos-Silva, P. R.; Deuster, P. A.; Curi, R.; Pithon-Curi, T. C. (Frontiers in Sports and Active Living, 2023)
Purpose: To investigate the effects of hydrolyzed whey protein enriched with glutamine dipeptide on the percentage of oxygen consumption, second ventilatory threshold, duration and total distance covered, and skeletal muscle damage during an exhaustion test in elite triathletes.